Infestation of Ixodidae Ticks in Cattle: Prevalence and Associated Risk Factors in Ambo District, Western Ethiopia - Addis Kassahun Gebremeskel; Berhanu Mekibib; Bekele Dabesa (East African Journal of Biophysical and Computational Sciences)
In Ethiopia, ticks cause serious economic loss particularly in ruminants. A cross sectional study was conducted in Ambo district, Western Ethiopia from October, 2018 to June, 2019 with the objectives of determining the prevalence, identifying the associated risk factors and the tick species of cattle in the area. From five purposively selected kebeles (the smallest administrative unit of Ethiopia) of the district, a total of 384 cattle were selected by systematic random sampling method. Adult Ixodid ticks were collected from different body parts of infested cattle, preserved in 10% formalin and transported to Ambo University Veterinary Parasitology Laboratory for stereomicroscopic identification to species level. Among 384 cattle examined, 201 (52.34%) cattle were infested with one or two tick species. A higher prevalence of tick infestation was recorded in Degele Gatira kebele (53.25%), followed by Abebe Doyo (50.65%), Gosu Kora (50.65%), Kisose Liban (50.65%), and Senkele Faris (56.59%). The study investigated three genera of Ixodid ticks namely Rhipicephalus (41.7%), Boophilus (0.8%) and Amblyomma (2.60%). Mixed infestations were common including Rh. Boophilus and Amblyomma 24(6.25%) and Rh. Boophilus and Rhipicephalus 4(1.04%). The study identified four species of ticks; namely Rh. (Bo.) decoloratus 109 (28.40%), Rhipicephalus (Boophilus) annulatus 43(11.20%), Amblyomma vareigatum 3(0.80%) and Rhipicephalus evertsi evertsi 11(2.90%). The difference in tick infestation was found to be statistically insignificant (P >0.05) between different age groups and kebeles but statistically significant (P <0.05) among sex groups, breeds, and different body condition scores (P <0.05). In conclusion, this study indicated a high prevalence of tick infestation and identified the most important ticks that can transmit various livestock diseases. A proper tick eradication campaign should be conducted to reduce the tick burden in the study area, and concomitantly reduce tick-borne diseases and associated economic losses.